The predictive power of sleep quality by morning-evening chronotypes, job satisfaction, and shift schedule in nurses: A cross-sectional study - Masumeh Hemmati-Maslakpak; Farzin Mollazadeh; Hossein Jamshidi (Wolters Kluwer Medknow Publications, 2021)
Background: Among nurses, sleep quality is an important factor which can be associated with many other factors, including job satisfaction, Morning-Evening (ME) chronotypes, and shift schedule. Besides, poor sleep quality can cause some problems for nurses and negatively affect the quality of nursing care. Therefore, the present study aimed to determine the predictive power of sleep quality by ME chronotypes, job satisfaction, and shift schedule in nurses working in Urmia teaching hospitals in 2019. Materials and Methods: A total of 327 nurses working in teaching hospitals affiliated to Urmia University of Medical Sciences were recruited using stratified sampling. Data were collected using the demographic questionnaire, the Pittsburgh Sleep Quality Index (PSQI), the Minnesota Satisfaction Questionnaire (MSQ), and the Composite Scale of Morningness (CSM). Data were analyzed using linear regression analysis and Pearson correlation coefficient. Results: The results of the Pearson correlation coefficient and linear regression analysis showed that the ME chronotypes (R2 = 0.51, p = 0.006), job satisfaction (R2 = 0.51, p = 0.001), and shift schedule (R2 = 0.51, p = 0.005) are significantly correlated with the sleep quality among nurses. Conclusions: We concluded that the sleep quality was correlated with ME chronotypes, job satisfaction, and shift schedule, so that increased job satisfaction was associated with improved sleep quality, and the shift to the morning chronotype was associated with decreased sleep quality. Rotating shifts were also associated with higher sleep quality.